A Case Study of Inter-Institutional Collaboration - A tale of two cities? - McFarlane, D.; Cano, V.; Brown, K. (Proceedings of the International Conference on Networked Learning, 2000)
This paper will discuss the extent to which institutions are ready for collaborative relationships and will consider the operational difficulties and complexities of communication between partners at an institutional level. The case will examine the relationship between members of academic staff at Glasgow Caledonian University (GCAL) and Queen Margaret University College (QMUC) within a collaborative research project in the area of web-based learning. Whilst this account presents merely the data of one web-based learning implementation, the nature of the problems suggest that they might not be unique across the sector.